Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/290161
|View full text |Cite
|
Sign up to set email alerts
|

Proteases of Wood Rot Fungi with Emphasis on the GenusPleurotus

Abstract: Proteases are present in all living organisms and they play an important role in physiological conditions. Cell growth and death, blood clotting, and immune defense are all examples of the importance of proteases in maintaining homeostasis. There is growing interest in proteases due to their use for industrial purposes. The search for proteases with specific characteristics is designed to reduce production costs and to find suitable properties for certain industrial sectors, as well as good producing organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 76 publications
0
22
0
2
Order By: Relevance
“…Cultivations that are performed in the vegetative phase are much more interesting and functional for research considering that they can be kept in the laboratory, performed on a small and medium scale, and important parameters such as temperature, humidity, pH and aeration can be easily controlled (Inácio et al, 2015a). Thus, submerged cultivation is a promising and still under-explored alternative for the extraction of bioactive molecules in short time, which also allows the mycelia storage for a long period without genetic alterations, beneficiating the conservation of biodiversity (Zilly et al, 2011).…”
Section: Submerged Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivations that are performed in the vegetative phase are much more interesting and functional for research considering that they can be kept in the laboratory, performed on a small and medium scale, and important parameters such as temperature, humidity, pH and aeration can be easily controlled (Inácio et al, 2015a). Thus, submerged cultivation is a promising and still under-explored alternative for the extraction of bioactive molecules in short time, which also allows the mycelia storage for a long period without genetic alterations, beneficiating the conservation of biodiversity (Zilly et al, 2011).…”
Section: Submerged Cultivationmentioning
confidence: 99%
“…Extensive research on cultivation techniques (Gregori, Svagelj & Pohleven, 2007;Carvalho, Sales-Campos & Andrade, 2010), chemical composition and nutritional profile (Reis et al, 2012;Atri et al, 2013;Maftoun et al, 2015) has been done in the last ten years, along with a comprehensive account of the biotechnological capabilities of the genus Pleurotus including enzyme production (Inácio et al, 2015a;Knop, Yarden & Hadar, 2015) (Figure 2). More recently, the scientific reports referring to Pleurotus species have also focused on novel approaches for taxonomic issues (Menolli Jr., Breternitz & Capelari, 2014;Maftoun et al 2015), isolation and characterization of new functional compounds, besides the in depth-study of their medicinal properties (Khan & Tania, 2012;Patel, Narain & Singh, 2012;Yahaya, Rahman & Abdulhah, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pepsin has broad specificity with a preference for peptides containing linkages with hydrophobic amino acids and preferentially cleaves C‐terminal to Phe and Leu. Whereas, Pleurotus eryngii possesses a pool of acid and basic proteases (Inácio et al , ) belonging to the families of aspartyl (Wang & Ng, ), serine (Cha et al , ) and metalloproteases (Shen et al , ), characterised by different active sites that hydrolyse the protein in several sites simultaneously, thus leading with a consequent increase in DH value. As shown in Table , DH values were significantly influenced by the CN haplotype ( P < 0.001), in agreement with Petrat‐Melin et al () who reported that the haplotype influences positively or negatively the presence of zones resistant to enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, several commercial protease preparations, namely Alcalase ® , Neutrase ® and Flavourzyme ® based on bacterial and fungal peptidases are widely used for the synthesis of bioactive peptides (De Castro & Sato, ; Bhat et al , ; Silva, ). Among the mushrooms, those of the Pleurotus genus produce different types of proteases; in particular, Pleurotus eryngii , one of the most popular edible mushrooms worldwide, is an excellent producer of aspartic and serine proteases (Inácio et al , ). Moreover, Pleurotus eryngii contains various beneficial bioactive compounds such as polyphenols, polysaccharides, peptides and dietary fibres (Ferreira et al , ); thus, it is widely utilised in the food industry for developing dairy functional foods (Miao et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, proteases play an essential role in the food industry, acting as agents for modifying the functional properties of proteins, in the processing of cheese, in obtaining protein hydrolyzates, improving the flavor of some foods and also in baking (Inacio et al, 2015). These enzymes participate in some physiological processes such as sporulation, conidial discharge, germination, regulation of gene expression and protein turnover (Khaund and Joshi, 2014).…”
Section: Introductionmentioning
confidence: 99%